2013
DOI: 10.1159/000356584
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Chloride Secretion by Isoflavone Genistein in Endometrial Epithelial Cells

Abstract: Background /Aim: Genistein, the most active isoflavone found primarily in soybeans, alters ion transport functions in intestinal and airway epithelia. The present study aims to investigate the acute effects and mechanisms of action of genistein in immortalized porcine endometrial epithelial cells. Methods: Ussing chamber technique was used for transepithelial electrical measurements. Results: Genistein increased short-circuit currents (Isc) which were inhibited by glibenclamide, NPPB, CFTRinh-172, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…This observation may correlate with our previous study demonstrating an acute effect of Ge on stimulation of chloride secretion in endometrial cells (Deachapunya & Poonyachoti 2013). Thus, the reduction in transcellular resistance caused by the opening of chloride ion-conductive pathway may account for the Ge-induced decrease in TER, albeit the TER is mainly dependent on the paracellular pathway (Madara et al 1988).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This observation may correlate with our previous study demonstrating an acute effect of Ge on stimulation of chloride secretion in endometrial cells (Deachapunya & Poonyachoti 2013). Thus, the reduction in transcellular resistance caused by the opening of chloride ion-conductive pathway may account for the Ge-induced decrease in TER, albeit the TER is mainly dependent on the paracellular pathway (Madara et al 1988).…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated that Ge and Di at specific concentrations affected the barrier function by alterations in TJ permeability in immortalized glandular epithelial monolayer, which have previously represented as an effective model for evaluating the effect of phytoestrogen on electrolyte transport (Deachapunya & Poonyachoti 2013). The underlying mechanism of these effects was thought to be relevant to alterations in TJ proteins, claudins, and ZO expression, as the genomic effects of these two isoflavonoids have been reported to affect the transcription level of these TJs proteins in intestinal epithelial cells (Suzuki & Hara 2009).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A similar stimulatory effect on CFTR channel activity was also observed by another citrus-derived flavonoid, tangeretin [7]. Because of its therapeutic potential in treating CF [41], the best-known and studied flavonoid, which can stimulate CFTR-dependent Cl - secretion, is genistein [42]. Genistein is a potent activator of CFTR and ∆F508 CFTR in human airway epithelial cell lines [43].…”
Section: Discussionmentioning
confidence: 81%